Tourism Impacts on Indigenous Pastoral Communities in China - Fan, Mingming; Wenjun Li; Guohong Wei; Fang Luo (Rangeland Ecology & Management, 2015)
Abstract In China, booming tourism is considered to be a win-win solution to fight both ecosystem degradation and poverty in pastoral areas. However, whether this alternative livelihood can reduce pressure on rangeland and improve livelihood of indigenous peoples has not yet been explored. To examine tourism’s impacts on pastoral communities, we conducted field surveys at Inner Mongolia and Xinjiang and distributed questionnaires in 12 provinces including most of the grassland areas of China. On the basis of fieldwork and national survey data, we found that different types of operations have different impacts on livelihood and ecosystem in pastoral area. Pastoralists involved in tourism can increase the income of pastoral households during the summer tourism season, but that pastoralism still provides the main guarantee of a sustainable livelihood. However, along with the development of tourism, business enterprises from outside the pastoral area may replace local herders in tourism operations. As a result, a large area of rangeland may be lost to local herders, who only receive money if they rent their pastures or serve as laborers; unfortunately, many residents lack the training to perform better-paid roles. In addition, we found that pure tourism that replaces pastoralism does not necessarily protect the rangeland, as it brings a variety of environmental impacts and disrupts traditional use that the rangeland may be adapted to. On the basis of our findings, we recommend that tourism managed by local operators who also engage in pastoralism should become the main direction for economic development.
Keywords: economy of pastoral areas; Inner Mongolia; pastoralism; perceptions of ecosystem change; sustainable tourism; Xinjiang